KNOWLEDGE, EXPERIENCE, FINANCIAL SATISFACTION, AND INVESTMENT DECISIONS: GENDER AS A MODERATING VARIABLE - Tri Kartika Pertiwi; Nuruni Ika Kusuma Wardani; Icasania Septentia (Jurnal Manajemen dan Kewirausahaan, 2021)
This research aimed to analyze and examine the effect of financial experience, financial knnowledge, and financial satisfaction to the decision making of investor’s investment with gender as a moderation variable. The method of analysis employed was Partial Least Square (PLS). Meanwhile, the research result showed that the knowledge variable, experience, and financial satisfaction significantly affected to the decision making of investment. However, gender as a moderation variable was not significantly strengthening to that relationship. Finally, it could be concluded that in decision making we had to consider several factors like knowledge, experience, and satisfaction in efforts to increase the investor’s prosperity or well-being.